Non-equilibrium ionization in the multiphase circumgalactic medium -- impact on quasar absorption-line analyses - Suyash Kumar; Hsiao-Wen Chen (The Open Journal of Astrophysics)
This paper presents an updated framework for studying the ionizing conditions and elemental abundances of photoionized, metal-enriched quasar absorption systems. The standard assumption of ionization equilibrium invoked in absorption line analyses requires gas to cool on longer timescales than ionic recombination ($t_\mathrm{cool} \gg t_\mathrm{rec}$). However, this assumption may not be valid at high metallicities due to enhanced cooling losses. This work presents a suite of time-dependent photoionization (TDP) models that self-consistently solve for the ionization state of rapidly cooling gas irradiated by the extragalactic ultraviolet background (UVB). The updated framework explores various revised UVBs from recent studies, a range of initial temperatures, and different elemental abundance patterns to quantify the effects of TDP on the observed ion fractions. A metal-enriched ($\mathrm{[\alpha/H]}=0.6_{-0.1}^{+0.2}$) \ion{C}{IV} absorption system at $z \sim 1$ previously studied using photoionization equilibrium (PIE) models is re-examined under the TDP framework. The main findings are as follows: (1) varying prescriptions for the underlying UVB or \magenta{adopting initial temperatures $T_0 \lesssim 10^6 \ \mathrm{K}$ (with the starting ionization state in collisional equilibrium)} change TDP ion fractions by up to a factor of three and ten respectively, but the adopted relative elemental abundance pattern affects ion fractions by at most 40\%; (2) the inferred gas densities are consistent between PIE and TDP, but under TDP solar metallicity cannot be ruled out at more than 2-$\sigma$ significance and a non-solar [C/$\alpha$]$\approx 0.25$ is robustly constrained from the observed relative ion abundances. Extending the TDP analyses to a larger sample of super-solar absorption components with high signal-to-noise absorption spectra is needed to quantify the fraction of metal absorbers originating in rapid cooling gas.